2017
DOI: 10.1177/1010428317701639
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pretreatment inflammatory biomarkers in advanced lung adenocarcinoma patients receiving first-line pemetrexed/platinum doublet

Abstract: Inflammation is a new hallmark feature of cancer initiation and progression. We aimed to investigate the association between inflammatory response biomarkers and progression-free survival and overall survival in advanced lung adenocarcinoma patients treated with first-line pemetrexed and platinum doublet chemotherapy. Patients hospitalized between April 2012 and March 2015 were enrolled and eliminated according to the inclusion and exclusion criteria. The pretreatment neutrophil-to-lymphocyte ratio, lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…Unlike NLR, multivariate analysis in this study did not reveal any proof of a connection between dNLR and staging, LNM, or DM. NLR and dNLR look identical and have similar effects on cancer-specific mortality [91,92]. Our investigation supported this hypothesis, which found a robust positive correlation between dNLR and NLR (ρ = 0.950, p < 0.001).…”
Section: Discussionsupporting
confidence: 85%
“…Unlike NLR, multivariate analysis in this study did not reveal any proof of a connection between dNLR and staging, LNM, or DM. NLR and dNLR look identical and have similar effects on cancer-specific mortality [91,92]. Our investigation supported this hypothesis, which found a robust positive correlation between dNLR and NLR (ρ = 0.950, p < 0.001).…”
Section: Discussionsupporting
confidence: 85%
“…A total of 23 studies comprising 8361 lung cancer patients were included. 7 -10,12 -30 Among these patients, 5702 (68%) were males, 4548 were current smokers and 2212 were diagnosed with squamous carcinoma. The main features of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The dNLR had been assessed as a predictor of treatment outcomes in other tumors receiving immunotherapy (62) or chemotherapy (63,64). In lung cancer, dNLR was a prognostic biomarker of the immunotherapy (65) and chemotherapy (22) outcome. Besides dNLR, prognostic tools integrating some items are also under investigation, including tumor immune dysfunction and exclusion (66), lung immune prognostic index (65), and the Glasgow prognostic score (67).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil-to-lymphocyte ratios (NLR), defined as the absolute neutrophil count (ANC) divided by the absolute lymphocyte count (ALC) from whole blood, can be easily and inexpensively accessed from regular blood tests and are associated with the prognosis of various cancers (13,14), including lung cancer (15,16). Our previous study indicated that elevated pretreatment NLR is an independent predictor of inferior survival for NSCLC patients receiving chemotherapy (17), which has been conflicted (18)(19)(20) and supported (21)(22)(23)(24) by other studies. To our knowledge, no consensus on this relationship has been reached and there are a lack of recent meta-analyses (MAs) that comprehensively assess the relationship between pretreatment NLR and systemic treatment outcomes for NSCLC.…”
Section: Original Articlementioning
confidence: 99%